Pelaksanaan Eksekusi Hak Tanggungan yang Tidak Didaftarkan Di Kantor Badan Pertanahan - Baiq Nuansa Fitria (Jatiswara, 2017)
The purpose of this study was to determine and analyze the fund execution of mortgages rights and legal effects arising from the execution of mortgages that are not registered to the office of land agency.The research method that used in this study was Normative legal research and Empirical law research, with the legislation approach, conceptual, and sociological. Data analysis and legal materials was done by analyzing the various regulations that specifically regulate the rights of dependents as well as analyzing the findings data on the fields that related to practice of unregistered mortgages.Based on the results of the research, the creditor can still execute mortgages that are not registered in the office of land agency, by means that there is a guarantee from Notary in the form of Covernote. The creditor refers to the Power of Attorney for Load Rights (SKMHT) which has been made with the Deed of Assignment Rights (APHT) in the presence of a Notary or PPAT, and asks PPAT to register the Mortgage Right at the Office of Land Agency, with time limit of 3 (three) month maximum.The legal consequences of the execution of an unregistered mortgage cause the creditor of the mortgage does not have the position of the preferred creditor, but the same as the position of the concurrent creditor. From the decline of the creditor's status, because it does not meet the fundamental and conditions that require mortgage rights are registered. As well as mortgage rights can coused invalidated by law.